2022
DOI: 10.1590/1983-1447.2022.20210038.en
|View full text |Cite
|
Sign up to set email alerts
|

Caring for elderly people during the COVID-19 pandemic: the experience of family caregivers

Abstract: Objective To build a theoretical model that represents the experience of family caregivers of elderly people during the COVID-19 pandemic. Method Qualitative study that used the Grounded Theory as a methodology, carried out in Minas Gerais State in August 2020. 16 caregivers were interviewed. Results Uncomfortable emotions emerged and drove the caregivers’ actions to: adopt preventive measures to protect the elderly from contracting the coronavirus; guarantee their healthcare; and make them aware of the pand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In the case of long-term caregivers and those looking after patients with dementia and other neurodegenerative diseases, somatic problems are more common [19,20]. Other research also highlighted the impact on emotions related to anguish, impotence, insecurity, fear, worry, and sadness [21]. In order to confront these stressors and attempt to reduce the impact of the pandemic on their health and their role as providers of care, caregivers implemented strategies that included adapting to the available support and the new ways of communicating with health service professionals [22], although no evidence has been found that these strategies have been explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of long-term caregivers and those looking after patients with dementia and other neurodegenerative diseases, somatic problems are more common [19,20]. Other research also highlighted the impact on emotions related to anguish, impotence, insecurity, fear, worry, and sadness [21]. In order to confront these stressors and attempt to reduce the impact of the pandemic on their health and their role as providers of care, caregivers implemented strategies that included adapting to the available support and the new ways of communicating with health service professionals [22], although no evidence has been found that these strategies have been explored in depth.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of long-term caregivers and those looking after patients with dementia and other neurodegenerative diseases, somatic problems are more common [19,20]. Other research also highlighted the impact on emotions related to anguish, impotence, insecurity, fear, worry and sadness [21]. In order to confront these stressors and attempt to reduce the impact of the pandemic on their health and their role as a providers of care, caregivers implemented strategies that included adapting to the available support and the new ways of communicating with health service professionals [22], although no evidence has been found that these strategies have been explored in depth.…”
Section: Introductionmentioning
confidence: 99%